A review of free flap failures in the University Hospital, Kuala Lumpur - Ahmad, T.S.; Musa, G.; Lee, J.K. (Academy of Medicine, Singapore, 1997)
Sixty-one free flaps performed in 59 patients from April 1983 to April 1995 were analysed. Various factors that might have affected the outcome of the surgery were studied. These included the patient's age, history of smoking, pre-existing medical problems such as hypertension and diabetes mellitus, the type of free flaps, flap infection, use of postoperative anticoagulation, postoperative anaemia and re-exploration. The infection rate was 16.4% and this had a strong correlation with the free flap failure in our study population. Postoperative anaemia could adversely affect the tissue oxygenation of the free flap and delay the re-exploration due to the high anaesthetic risk. Dextran was routinely used for postoperative anticoagulation. There were also rescue attempts using heparin infusion when needed. The overall failure rate was 13.1%. Besides good anaesthetic support, a well-prepared protocol is necessary both for the preoperative planning of free flap surgery as well as salvaging a failure.